Overlapping action of T3 and T4 during Xenopus laevis development - Tribondeau, Alicia; Du Pasquier, David; Benchouaia, Médine; Blugeon, Corinne; Buisine, Nicolas; Sachs, Laurent M. (Frontiers in Endocrinology, 2024)
Thyroid hormones are involved in many biological processes such as neurogenesis, metabolism and development. However, compounds called endocrine disruptors can alter thyroid hormone signaling and induce unwanted effects on human and ecosystems health. Regulatory tests have been developed to detect these compounds, but need to be significantly improved by proposing novel endpoints and key events.The Xenopus Eleutheroembryonic Thyroid Assay (XETA, OECD test guideline n°248) is one such test. It is based on Xenopus laevis tadpoles, a particularly sensitive model system for studying the physiology and disruption of thyroid hormone signaling: amphibian metamorphosis is a spectacular (thus easy to monitor) life cycle transition governed by thyroid hormones. With a long-term objective of providing novel molecular markers under XETA settings, we propose first to describe the differential effects of thyroid hormones on gene expression, which, surprisingly, are not known. After thyroid hormones exposure (T3 or T4), whole tadpoles RNAs were subjected to transcriptomic analysis. By using standard approaches coupled to system biology, we found similar effects of the two thyroid hormones. They impact the cell cycle and promote the expression of genes involves in cell proliferation. At the level of the whole tadpole, the immune system is also a prime target of thyroid hormone action.